20th century photographers : Interviews on the craft, purpose, and the passion of photography - Schaub, Grace; Schaub, George (Focal Press, 2015)
"This book is a compilation of interviews and essays that cover a broad range of photographers and photographic disciplines. Each photographer profiled made a living by concentrating on a specific aspect of the craft, but in doing so transcended their livelihood to become recognized for more than the type of images they created. Each had a distinct "style," creative approach, dedication to the craft, point of view about themselves and the world. These interviews were conducted during a seminal period in the shift from film to digital and from print reproduction to global distribution on the Internet. Just like their photographs continue to inspire today, now these pros' words can live on as an invaluable reference for the photographers of the future. The truth and wisdom in this collection transcend time and technology. - Features interviews with notable photographers including: Mary Ellen Mark, Carl Mydans, O. Winston Link, and Adam Newman - Covers a wide array of photographic fields such as photojournalism, fine art, and fashion. - Listen to the audio of many of the featured interviews on the book's companion website!"--